Intelijen Strategis BAKAMLA RI dalam Melaksanakan Kolaborasi Institusi Keamanan Maritim untuk Ketahanan Nasional - Sutisna, Muhammad; Rofii, Muhammad Syaroni, Mr. (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
Besides being asked to be an Archipelagoc State, almost all of Indonesia's territorial boundaries are surrounded by sea which places these waters as a strategic route because it is passed by international trade routes. Under these conditions, Indonesia must have a defense and security system that is capable of safeguarding its territory to deal with various military and non-military forces. Where a peaceful situation like this is dominated by non-military threats such as illegal fishing, human trafficking, drug smuggling by sea, to accidents and disasters at sea. So it takes institutions that have the power and authority to maintain maritime sovereignty and security. Although currently Indonesia already has the Indonesian Navy as a state institution that is responsible for maintaining Indonesian territorial sovereignty in the waters.This condition also motivated the author to conduct this research to see how the role of Bakamla RI in collaborating between maritime security institutions to strengthen national resilience considering the increasingly dynamic strategic environment requires a special formulation to overcome various kinds of problems that exist in Indonesian territorial jurisdictions. at the moment. Using a qualitative method approach through interviews and based on reference books and journals using three theories and concepts such as strategic intelligence, maritime security, and national security. The researcher wants to see how the collaborative role of the Indonesian National Security Agency with the Indonesian Navy and Customs in maintaining maritime security is to strengthen national security. Keywoords: Archipelagoc State, defense, security, BAKAMLA RI, TNI AL, BNN, BEA CUKAI, Strategic Intelligence, Maritime Security, National, Security